2016
DOI: 10.1149/2.1111608jes
|View full text |Cite
|
Sign up to set email alerts
|

The Influences of Iodide Ion on Cu Electrodeposition and TSV Filling

Abstract: Through silicon via (TSV) technology has been researched for 3-dimensional packaging of electronic devices, and Cu electrodeposition has been used for TSV filling. The organic additives are one of the most important factors in Cu electrodeposition affecting Cu gap-filling, and the leveler usually plays a decisive role. In this research, iodide ion (I − ) is adopted instead of organic leveler for Cu bottom-up filling. The behaviors of I − are investigated by various types of electrochemical analyses. Especially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 35 publications
1
34
0
Order By: Relevance
“…The Cl − adsorbed on a Cu surface has been shown to activate Cu deposition, 55 but adsorbed I − suppresses Cu deposition. 56 The relatively covalent Cu−I bond is stronger than the relatively ionic Cu−Cl bond and involves a greater amount of charger transfer from I − to Cu. This stronger interaction between I − and Cu hinders atomic addition.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Cl − adsorbed on a Cu surface has been shown to activate Cu deposition, 55 but adsorbed I − suppresses Cu deposition. 56 The relatively covalent Cu−I bond is stronger than the relatively ionic Cu−Cl bond and involves a greater amount of charger transfer from I − to Cu. This stronger interaction between I − and Cu hinders atomic addition.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Addition of I – replaces Cl – on the {111} facet, leading to its passivation. The Cl – adsorbed on a Cu surface has been shown to activate Cu deposition, but adsorbed I – suppresses Cu deposition . The relatively covalent Cu–I bond is stronger than the relatively ionic Cu–Cl bond and involves a greater amount of charger transfer from I – to Cu.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The solution-based electrodeposition of metals has been extensively studied academically as well as provided industrial solutions for practical devices. , One interesting and applicable avenue of research has been the use of surface modifiers to affect the structure and morphology of deposited metals, for example, surfactants, organic molecules, and halide salts . In liquid-based electrochemical deposition, iodine adsorption on metal surfaces is well known to influence the kinetics of crystallization and the morphology of metal growth and has been frequently utilized to form compact, uniform films. For solid-state electrodeposition, several research teams have shown that modification of the lithium-metal surface has significantly improved the galvanic cycling properties using solid-state electrolytes; however, iodine adsorption has not been evident during the solid-state deposition of lithium metal nor has its influence on cell failure. Understanding the electrochemical interphase is a vital step to engineering practical SSBs.…”
Section: Introductionmentioning
confidence: 99%
“…To determine C I − in the target plating bath, a RC-CVS analysis was performed as follows: (1) assessment of Q 0 from the CVS analysis of the base solution (volume: 52 mL), (2) measurement of Q after adding the standard solution to the base solution (addition volume: 1 mL), (3) consecutive repetition (eight times) of the procedure (2) to generate a response curve, (4) preparation of a new bath and the appraisal of Q 0 (5), evaluation of Q t after adding the target solutions to the base solution (addition volume: 3 mL), ( 6) determination of C I − in the target solutions by interpolating the Q t /Q 0 value to the response curve by using Eq. 2. where C St was the known concentration of I − in the standard solution (400 μM), V T the addition volume of the target solution (3 mL), x * the addition volume value in the response curve at the same Q/Q 0 with Q t /Q 0 obtained from the target solution, and V V the pre-dosed volume of the base solution (52 mL).…”
Section: Methodsmentioning
confidence: 99%